Collective Violence and Social Disintegration: a Study of Mass Violence as a Trigger off Crime and The Loss of Social Values in Society - Utari, Indah Sri (The Indonesian Journal of International Clinical Legal Education, 2019)
Many offenders (both individual and collective) are not subject to legalsanctions. There are rules but rarely enforced it tends to favoritism, nocourts but often a nest of mafia-sale decision, and there is often adifficult decision but the judge executed. Consequently, there is nocertainty that the law is truly objective norms that apply to all. There isno assurance that the process through the courts produce truth andjustice. That is why, difficult to ascertain that the person who is foundguilty, should always be punished. In fact there is a tendency todiscriminatory treatment between the perpetrators of the crime ofordinary citizens and the economically weak with perpetrators of crimescategorized as a strong economy, government officials, and even theperpetrators of environmental law enforcement officers themselves. Asa result of further emerging collective disappointment against legalinstitutions. People lose motivation to obey the law. Society tends tonot believe in the legal process, are not sure to get justice through thelaw, and appeared permissiveness of violations (Tanya, 2011: 5-6).Over the past few years, poverty has widened, many public serviceshave been fraudulently cheating. Not only have people stopped soeasily breaking the law and vigilante without hesitation, corruptiontakes place in every space, the abuse of power continues, scandals arise,reproductive violence everywhere including within the academiccommunity, and people increasingly poor again suffer Without theempathy of the elite and the possessed. This is where the necessity ofCLE is done in the framework of student vision in reality, so thatstudents do not study empty space but more on real observations inthe community, which then conducted the assessment in searching forthe right solution .Such circumstances must necessarily be terminated.All components of the nation must work together to build a communityof love. The republican community inhabited by the children of theemphatic nation is encouraged to give the best for the nation, able topraise the virtues, always live honorably, abstain from harming others,not to hold back what others deserve, and the generosity and love ofothers